Finding Satisfaction in Belonging: Preservice Teacher Subjective Well-Being and its Relationship to Belonging, Trust, and Self-Efficacy - Bjorklund Jr., Peter; Warstadt, Melissa F.; Daly, Alan J. (Frontiers in Education, 2021)
The well-being of teachers and preservice teachers has been a topic extensively explored through the lens of burnout and stress. Despite its manifold benefits, few studies have explored PST well-being through the lens of subjective well-being. Grounding our study in positive psychology, we explore the relationships between preservice teachers’ subjective well-being, program sense of belonging, relational trust, and self-efficacy. Our participants included 63 multiple- and single-subject preservice teachers in a major university teacher education program in the western United States. They were surveyed in May 2019 in the final month of completing their program. We found that sense of belonging, relational trust, and self-efficacy individually are positively associated with well-being. A mediation analysis revealed that the relationship between relational trust and subjective well-being is mediated by program sense of belonging, which may indicate the importance of cohesion in a cohort-based teacher education program.